2017
DOI: 10.7769/gesec.v8i2.576
|View full text |Cite
|
Sign up to set email alerts
|

Um Modelo Multicritério Construtivista Para Apoiar À Gestão Da Atividade De Pesquisa Da Universidade De Mindelo

Abstract: Este estudo tem como objetivo construir um modelo de avaliação de desempenho para apoiar à gestão da atividade de pesquisa da Universidade de Mindelo (UM), sediada em Cabo Verde, na África. Para tal, utilizou-se, como instrumento de intervenção, a Metodologia Multicritério de Apoio à Decisão-Construtivista (MCDA-C). A aplicação dessa metodologia permitiu a geração de conhecimento no pró-reitor de pesquisa da UM para identificação dos aspectos relevantes, necessários e suficientes, segundo a sua percepção, para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…It is understood that this result comes from the constructivist characteristic of MCDA-C methodology, which analyzes that the proposed model is customized to the application context (Cardoso et al, 2017). In this way, the particularities and attributes of the IFSC library -Araranguá campus and the librarian's perception were respected in the construction of indicators in the model structuring phase.…”
Section: Stakeholders Decision-maker Campus Librarianmentioning
confidence: 99%
See 3 more Smart Citations
“…It is understood that this result comes from the constructivist characteristic of MCDA-C methodology, which analyzes that the proposed model is customized to the application context (Cardoso et al, 2017). In this way, the particularities and attributes of the IFSC library -Araranguá campus and the librarian's perception were respected in the construction of indicators in the model structuring phase.…”
Section: Stakeholders Decision-maker Campus Librarianmentioning
confidence: 99%
“…Thus, once the label and the actors involved were defined, the Primary Evaluation Elements (PEEs) were identified, which are qualities or characteristics that the decision-maker considers important and/or that impact their values and preferences regarding the context (Ensslin et al, 2013;Ensslin et al, 2010). From the identification of the PEEs, the concepts that guide the direction of preference were constructed, pertinent to the PEE and which is followed by its psychological opposite (minimum permissible of the underlying objective), represented by ellipsis (...) that sould be read as "rather than" (Cardoso et al, 2017). However, it is observed that a PEE can unfold in more than one concept (Ensslin et al, 2013;Ensslin et al, 2010).…”
Section: Stakeholders Decision-maker Campus Librarianmentioning
confidence: 99%
See 2 more Smart Citations
“…Faced with this difficulty, the relevance of the construction of unique models, still incipient in the literature focused on universities, which recognizes the organization as unique both in terms of its managers, as well as its potential and vulnerability. The MCDA-C methodology, used in this case study, was developed by the Laboratory of Multicriteria Methodologies for Decision Support (LabMCDA) of the Federal University of Santa Catarina (CARDOSO et al, 2017). The MCDA-C approach seeks to expand the knowledge of the decision-maker in complex, conflicting and uncertain scenarios Ensslin et al, 2000).…”
Section: Review Of the Literature 21 Evaluation Of Performance In Uni...mentioning
confidence: 99%